Molecular and Functional Study of Transient Receptor Potential Vanilloid 1-4 at the Rat and Human Blood–Brain Barrier Reveals Interspecies Differences - Luo, Huilong; Saubamea, Bruno; Chasseigneaux, Stéphanie; Cochois, Véronique; Smirnova, Maria; Glacial, Fabienne; Perrière, Nicolas; Chaves, Catarina; Cisternino, Salvatore; Declèves, Xavier (Frontiers in Cell and Developmental Biology, 2020)
TRPV1-4 expression and functionality were investigated in brain microvessel endothelial cells (BMEC) forming the blood-brain barrier (BBB) from rat and human origins. In rat, Trpv1-4 were detected by qRT-PCR in the brain cortex, brain microvessels, and in primary cultures of brain microvessel endothelial cells (rPBMEC). A similar Trpv1-4 expression profile in isolated brain microvessels and rPBMEC was found with the following order: Trpv4 > Trpv2 > Trpv3 > Trpv1. In human, TRPV1-4 were detected in the BBB cell line hCMEC/D3 and in primary cultures of BMEC isolated from human adult and children brain resections (hPBMEC), showing a similar TRPV1-4 expression profile in both hCMEC/D3 cells and hPBMECs as follow: TRPV2 >> TRPV4 > TRPV1 > TRPV3. Western blotting and immunofluorescence experiments confirmed that TRPV2 and TRPV4 are the most expressed TRPV isoforms in hCMEC/D3 cells with a clear staining at the plasma membrane. A fluorescent dye Fluo-4 AM ester was applied to record intracellular Ca2+ levels. TRPV4 functional activity was demonstrated in mediating Ca2+ influx under stimulation with the specific agonist GSK1016790A (ranging from 3 to 1000 nM, EC50 of 16.2 ± 4.5 nM), which was inhibited by the specific TRPV4 antagonist, RN1734 (30 µM). In contrast, TRPV1 was slightly activated in hCMEC/D3 cells as shown by the weak Ca2+ influx induced by capsaicin at a high concentration (3 µM), a highly potent and specikfic TRPV1 agonist. Heat-induced Ca2+ influx was not altered by co-treatment with a selective potent TRPV1 antagonist capsazepine (20 µM), in agreement with the low expression of TRPV1 as assessed by qRT-PCR. Our present study reveals an interspecies difference between Rat and Human. Functional contributions of TRPV1-4 subtype expression were not identical in rat and human tissues reflective of BBB integrity. TRPV2 was predominant in the human whereas TRPV4 had a larger role in the rat. This interspecies difference from a gene expression point of view should be taken into consideration when modulators of TRPV2 or TRPV4 are investigated in rat models of brain disorders.